PERANCANGAN APLIKASI SISTEM INFORMASI PARIWISATA BERBASIS WEB DI KABUPATEN NAGEKEO PROVINSI NUSA TENGGARA TIMUR DENGAN METODE LOCATION BASED SERVICE (LBS) - Teang, Beatriks Diana; Faizah, NM; Nurcahyo, Widyat (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2023)
The research objectives are; designing a web-based information system that provides information about tourist attractions, culinary delights, and lodging in the Nagekeo district. In the application development process using the Rapid Application Development (RAD) method and modeling design using Data Flow Diagrams (DFD). From the discussion that has been described, it can be concluded that the results of this study tourists can easily and quickly get information about tourist objects, culinary, lodging around tourist sites in Nagekeo district. It is estimated that tourism development technology will continue, which is a big opportunity for companies and destinations, especially in Indonesia. There is a need for studies on tourists on cultural experiences, streaming platforms, metaverse technology, biometric payment methods so that there are innovations to attract visitors and add value to the local tourism industry through the implementation of digital solutions.